2001
DOI: 10.1021/om000868y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Sterically Encumbered Unsymmetrical 9-Borafluorene, Its Pyridine Adduct, and Its Dilithium Salt

Abstract: The reaction of 2,6-(4-t-BuC 6 H 4 ) 2 C 6 H 3 Li with BH 2 Cl‚SMe 2 in hexane or Et 2 O solution affords the terphenyl-substituted unsymmetrical 9-borafluorene 1-(4-tert-butylphenyl)-7-tertbutyl-9-(bis-2,6-(4-tert-butylphenyl)phenyl)-9-borafluorene (1) in good to moderate yields. Addition of pyridine gives the colorless crystalline adduct 1‚py. Compound 1 is readily reduced to the deep red heteroaromatic dianionic (µ 2 -η 5 ,η 5 -1-(4-tert-butylphenyl)-7-tert-butyl-9-(bis-2,6-(4-tert-butylphenyl)phenyl)-9-bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 47 publications
(70 reference statements)
4
27
0
2
Order By: Relevance
“…The BÀN bond in 1 b (1.6567 (3) ) is considerably longer than that in the chloroborole 4-picoline adduct (1.6022(3) ), [9b] and the sterically highly hindered borafluorene systems (1.638 (3) ). [10] In fact, the value in 1 b is much more comparable to that observed in the aforementioned FLP of B(C 6 F 5 ) 3 and 2,6-lutidine, which dissociates at room temperature in solution. [11] In comparison with PPB, the molecular structure of 1 b reveals significant strain, as shown by the torsion angles of the borole.…”
supporting
confidence: 62%
“…The BÀN bond in 1 b (1.6567 (3) ) is considerably longer than that in the chloroborole 4-picoline adduct (1.6022(3) ), [9b] and the sterically highly hindered borafluorene systems (1.638 (3) ). [10] In fact, the value in 1 b is much more comparable to that observed in the aforementioned FLP of B(C 6 F 5 ) 3 and 2,6-lutidine, which dissociates at room temperature in solution. [11] In comparison with PPB, the molecular structure of 1 b reveals significant strain, as shown by the torsion angles of the borole.…”
supporting
confidence: 62%
“…It has been shown that this ligand has the tendency for facile intramolecular C-H bond activation of the ortho position of the outer phenyl ring, which may serve as a mechanism to form an in situ generated bidentate ligand that provides robust steric protection for the metal center [9]. The literature reveals a paucity of reports of 2,6-di(4-t-butylphenyl)phenyl based group 13 compounds [10,11]. The reactivity of RLi (R = 2,6-(4-t-BuC 6 H 4 ) 2 C 6 H 3 ) with group 13 metals was of interest, as to ascertain the stability and structural properties of the ligand-metal complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Besides these three widely applied approaches, which can assemble 9-aryl-9-borauorenes in one step, the Wehmschulte group synthesized two unsymmetric 9-borauorenes (2a and 2b, Scheme 3, path h) in one step by using H 2 ClB$SMe 2 as the boron source. 75,76 The formation of the borole ring takes place via a facile intramolecular C-H activation process, but the requirement of bulky terphenyl precursors limits its further application.…”
Section: Introductionmentioning
confidence: 99%